Primary Aldosteronism and Pregnancy - Tomáš Zelinka; Ondřej Petrák; Ján Rosa; Robert Holaj; Branislav Štrauch; Jiří Widimský Jr (Karger Publishers, 2020)
Objective: Primary aldosteronism (PA) may present at younger age and may thus complicate pregnancy. Our aim was to identify female patients in whom PA was diagnosed after pregnancy complicated with hypertension and to analyze possible hypertension-related complications during pregnancy. Methods: We performed retrospective analysis of female patients with PA diagnosed and treated at our Department who were pregnant before the diagnosis of PA. Results: We found 14 patients with PA (age at diagnosis 32.2 ± 4.2 years, hypertension duration 5.4 ± 3.6 years) suffering from hypertension 3 (IQR 0, 4) years before pregnancy (6 patients had hypertension diagnosed during pregnancy). Three subjects were pregnant twice, and 1 patient had been pregnant three times before the final diagnosis of PA was made. Ten subjects delivered by Caesarean section (in 3 cases due to early-onset preeclampsia and 2 subjects due to significantly increased blood pressure), and 9 cases spontaneously (1 subject complicated twice due to late-onset preeclampsia). Preterm delivery occurred in 5 cases - the earliest one in the sixth month of gestation. Subsequent diagnosis of PA (sometimes with a long delay up to a maximum of 12 years) was made on the basis of significantly low potassium values (2.7 ± 0.4 mmol/L; 2 subjects even suffered from muscle cramps) and hypertension (mostly moderate), elevated plasma/serum aldosterone (54.1 ± 20.2 ng/dL) and suppressed plasma renin activity (0.4 ± 0.2 ng/mL/h) or plasma renin (1.9 ± 1.6 ng/L). Thirteen subjects underwent laparoscopic adrenalectomy (in all but 2 cases, diagnosis of a large cortical adenoma [16 ± 5.9 mm] was made), and 1 subject was classified with bilateral hyperplasia according to adrenal venous sampling. Operation normalized BP in 10 subjects and improved BP control in the remaining 3 subjects. Two patients became pregnant after adrenalectomy, and their pregnancies were uneventful. Conclusion: PA is associated with a high rate of pregnancy-related complications. The most frequent complication is preeclampsia, in some cases leading to preterm delivery. The optimal prevention of these complications is early diagnosis of PA, and in these particular hypertensive cases, the awareness of hypokalemia.